Pediatric patients clinical-epidemiological characterization with suicide attempt at the Holguín Provincial Pediatric Hospital - Nilda Ramona Sarmiento Ardebol; Jorge Antonio Fernández Carballo; Dayana María Fernández Sarmiento; Frank Miguel Hernández Velázquez (Medisur)
Background: suicide attempts in pediatric ages are a current problem with a growing trend worldwide. This group is very vulnerable to the action of internal and external factors that alter their integrity. In Cuba, despite the achievements in this regard, it is also considered a mental health problem. Objective: to characterize, from the clinical and epidemiological point of view, pediatric patients with suicide attempts. Methods: a descriptive, retrospective and cross-sectional study was carried out at the Octavio Concepción y de la Pedraja Provincial Pediatric Hospital, in the Holguín province, from January/2020 to December/2021. The entire universe was analyzed made up of 397 patients, treated at the hospital for suicide attempts during the studied period. The variables were: age, sex, origin and method used. Descriptive statistics were used. Results: patients aged between 16 and 18 years old (48.4%), female (74.6%) and urban origin (70.3%) predominated. 92.2% used the ingestion of psychotropic drugs as a method of suicide. Conclusions: the studied variables behave in a similar way to that described in other populations and contexts, in which adolescents from urban origin who ingested psychoactive drugs also predominated.